A Cross Sectional Study of the Prevalence of Obesity or Overweight and its Correlates among School Children in a Central India District - Srivastava, Dhiraj Kumar; Jain, Pankaj Kumar; Srivastav, Monika; Gour, Neeraj; Choubey, Bharati; Kumar, Sandip (National Journal of Community Medicine, 2017)
Introduction: The present century had noticed a rapid transition of society from undernourished and malnourished to overweight and overt obesity. This transition was initially reported in developed countries but now this phenomenon has been noticed in developing countries. The study was conducted to assess the knowledge about the obesity among school children and to find out the correlation between the knowledge and the actual BMI of the school children Material & Method: A List of all the students of class 6th -10th was gathered from the Principal’s office of selected school. The necessary information was collected using a pretested structured questionnaire. The information regarding weight, height and BMI was calculated using a standardized protocol. Result: A total of 921 student participated in the study. Most common age of participants was 14 to15 years. Overweight and obese were more prevalent among male students and students from private school. Majority of the participants were aware about the obesity. Watching television, playing video games, fast food intake, number of time breakfast slip and mean soda intake were significantly associated with obesity. Conclusion: Watching television, playing video games, fast food intake, number of time breakfast slip and mean soda intake were significantly associated with obesity